2021
DOI: 10.1097/olq.0000000000001544
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Disease Intervention: Exploring an Expanded Role for Partner Services in the MATRix-NC Demonstration Project

Abstract: Background: Disease intervention specialists (DIS) provide partner services for sexually transmitted infections (STIs). We assessed an expansion of DIS services for clients with HIV and/or syphilis, and contacts within their social and sexual networks.Methods: Black and Latinx cisgender men and transgender women who have sex with men diagnosed with HIV and/or syphilis in 4 urban North Carolina counties were referred to designated DIS, who were trained to recruit clients as "seeds" for chain-referral sampling o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 21 publications
(34 reference statements)
0
13
0
Order By: Relevance
“…Our cost analysis only covered 9 months of the MATRix-NC program, and Hurt et al 9 provide more complete information on the demographics of participants enrolled in the program. Consistent with data on HIV/STI patients in North Carolina, they found that MATRix-NC participants generally had lower levels of socioeconomic status 9,11 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our cost analysis only covered 9 months of the MATRix-NC program, and Hurt et al 9 provide more complete information on the demographics of participants enrolled in the program. Consistent with data on HIV/STI patients in North Carolina, they found that MATRix-NC participants generally had lower levels of socioeconomic status 9,11 .…”
Section: Discussionmentioning
confidence: 99%
“…Our cost analysis only covered 9 months of the MATRix-NC program, and Hurt et al 9 provide more complete information on the demographics of participants enrolled in the program. Consistent with data on HIV/STI patients in North Carolina, they found that MATRix-NC participants generally had lower levels of socioeconomic status 9,11 . Compared with initial seeds, peers were more commonly recruited from social networks than from sexual networks, and peers were significantly more likely to be heterosexual, cisgender women.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations